(3JCKjQ JNUU GdCSJGP aj JfejI GdegGQGJ GdMQcjI GdCSGSjI aj Xd GdHQfGeL GdQSej ddJQHjI GdHOfjI hGdQjGVjI Ydi HYV GdeJeOQSjf (B6 (3SfhGJ (B: (3OQGSI ejOGfjI Ydi eSJhi HYV GHJOGFjGJ HdOjI CbHh hdGjI HLGjIs - (3EOQjSj, Sdjes; (3HdhfjS, QTjOs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2023)
(3dbO gOaJ OQGSJfG Gdi eYQaI eG EPG cGf dJNUU GdCSJGP JCKjQ aj JfejI GdegGQGJ GdMQcjI GdCSGSjI dOi GdCWaGd GdeJeOQSjf aj GdWhQ GdGHJOGFj (B(6 (3SfhGJ(B) (3aj OGFQI CbHh, hcPG eYQaI eG EPG cGf dJNUU GdCSJGP JCKjQ aj JfejI GdegGQGJ GdMQcjI GdCSGSjI GdGfJbGdjI dOi GdCWaGd, hGdJYQa Ydi JCKjQ JNUU GdCSJGP aj JfejI GdegGQGJ GdMQcjI GdCSGSjI GdNGUI HJhGRf hKHGJ GdLSe ddCWaGd GdeJeOQSjf, h eG EPG cGf dJNUU GdCSJGP JCKjQ aj JfejI GdegGQGJ GdMQcjI GdCSGSjI GdNGUI HGdJMce hGdSjWQI dOi GdCWaGd GdeJeOQSjf aj GdWhQ GdGHJOGFj (B(6 (3SfhGJ(B) (3aj OGFQI CbHh(B. (3hbOG SJYedfG aj HMKfG GdefgL GdhUaj, HjfeG GTJedJ OQGSJfG Ydi YjfJjf, GdeLehYI GdChdi JMJ ETQGa CSGJPI eNJUjf aj GdJQHjI GdHOfjI hGdQjGVjI, hGdeLehYI GdKGfjI JMJ ETQGa CSGJPI ZjQ eNJUjf aj GdJQHjI GdHOfjI hGdQjGVjI, HMjK GMJhJ cd eLehYI Ydi (B188 (3Wad eJeOQS aj cdG GdeLehYJjf, ehRYjf Ydi (B4 (3EHJOGFjGJ, Cj Cf cd eLehYI JTed EHJOGFjJjf EKfJjf, hbO Je GdEYJeGO Ydi HWGQjI eJchfI ef (B(06) (3GNJHGQGJ, hbO GSJYedfG aj GdJMdjd GdEMUGFj ddHjGfGJ GdHQfGeL (BSPSS (3EUOGQ (B26(3, hHYO JMdjd hefGbTI GdfJGFL GdNGUI HGdaQVjGJ GdebJQMI GSJfJLfG Cf JNUU CSJGP GdJQHjI GdHOfjI hGdQjGVjI dg JCKjQ GjLGHj aj JfejI GdegGQGJ GdMQcjI GdCSGSjI ddCWaGd GdeJeOQSjf aj GdWhQ GdGHJOGFj(B. s
(3OcJhQGIs
Keywords: (3GdJYde h GdeQGbHI GdMQcjIs; (3Yde GdMQcIs